Output, Employment, Consumption, and Investment - Leontie, Wassily (Quarterly Journal of Economics, 1944)
I. The problem: quantitative relationship between the primary demand for particular products and total output and employment, 290. — II. Technological relations assumed, 294. — The resulting equations, 296. — Computing employment, 297. — The concept of final demand, 298. — III. Computation from American data for 1939, 299. — IV. Applicability of these results to data for 1929, 304. — Explanation of discrepancies, 308. — V. Relationship between final purchases of particular commodities and total employment, 311. — Appendix, 313.